2022
DOI: 10.26582/k.54.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Variability in performance indicators of the Netherlands women’s national handball team at the 2019 world championship

Abstract: The primary objective of this study was to discover the positional attack performance indicators of the winning Netherlands women’s national handball team during the 2019 World Championship in Japan. An ideographic, follow-up and multidimensional observational design was used to record and analyse positional attacks disputed in equal numbers of players (6v6) excluding attacks with an empty goal. Polar coordinates allowed us to determine behaviour patterns as well as performance indicators related to attack con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Handball is a technical-tactically, physically and psychologically complex sport that requires full engagement from players [ 1 , 2 ]. Factors that influence the performance of handball players are numerous, because of its complexity and structure.…”
Section: Introductionmentioning
confidence: 99%
“…Handball is a technical-tactically, physically and psychologically complex sport that requires full engagement from players [ 1 , 2 ]. Factors that influence the performance of handball players are numerous, because of its complexity and structure.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that for handball, the most relevant elements to training for improving performance are goalkeeper efficacy and distance shooting efficacy in order to determine whether to win or lose a match [ 8 ]. However, a recent study from Flores–Rodriguez & Alvite-de-Pablo [ 9 ] has demonstrated that the dynamic nature of offensive behaviors is highly relevant to determining goal efficacy.…”
Section: Introductionmentioning
confidence: 99%